2006
DOI: 10.1007/s10672-006-9007-x
|View full text |Cite
|
Sign up to set email alerts
|

Gathering Information and Exercising Influence: Two Forms of Civic Virtue Organizational Citizenship Behavior

Abstract: Political behavior at work often is disparaged as self-serving activity that undermines the efficient pursuit of organizational goals. Yet politics has a more benign meaning as well: responsible participation in decision-making processes, keeping informed, and promoting innovative ideas that serve long-term organizational interests. To date, the negative image of organizational politics among managers and scholars has limited research on the positive contributions of responsible political participation, a form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 59 publications
6
82
1
3
Order By: Relevance
“…Beyond above mentioned agreements, at simple correlations level, findings of this study showed that it is logical to consider civic virtue and organizational empathy as variables with clear ethical foundations (Graham, 2000;Kidder and Parks, 2001;Graham and Van Dyne, 2006;Butarbutar et al, 2010). Despite the fact that previous theories and studies propose ideas that organizational citizenship behaviors are ethical (and more particularly about civic virtue) (Ackfeldt and Cotte, 2005;Chun, 2005;Leung, 2007;Podsakoff et al, 2009;Ramachandran et al, 2011;Stewart Wherry, 2012), yet few studies so far clearly attempted to investigate these ethical foundations .…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Beyond above mentioned agreements, at simple correlations level, findings of this study showed that it is logical to consider civic virtue and organizational empathy as variables with clear ethical foundations (Graham, 2000;Kidder and Parks, 2001;Graham and Van Dyne, 2006;Butarbutar et al, 2010). Despite the fact that previous theories and studies propose ideas that organizational citizenship behaviors are ethical (and more particularly about civic virtue) (Ackfeldt and Cotte, 2005;Chun, 2005;Leung, 2007;Podsakoff et al, 2009;Ramachandran et al, 2011;Stewart Wherry, 2012), yet few studies so far clearly attempted to investigate these ethical foundations .…”
Section: Discussionmentioning
confidence: 62%
“…In initial formulation, civic virtue has been introduced as responsible participation in political life of the organization (Graham, 2000;Graham and Van Dyne, 2006). In fact civic virtue are considered participation beyond the call of duty in organizational meetings and gatherings with the aim of better and more effective involvement in organizational goals and missions (Graham, 2000;Kidder and Parks, 2001).…”
Section: Civic Virtue and Organizational Ethical Climatementioning
confidence: 99%
See 1 more Smart Citation
“…OCB has been described as courtesy that incorporates ''(a)dvance notice, reminders, passing along information, consultation, (and) briefing'' others about potential problems that may affect organizational outcomes (Organ, 1988, p. 12). OCB is sometimes defined as civic virtue that incorporates participating responsibly in the various activities of an organization, speaking up in the proper forum and in the appropriate manner (Graham, 1986), and gathering information and exercising influence (Graham and Van Dyne, 2006). OCB has also been framed as sportsmanship, or the patience to maintain a positive attitude and to ''tolerate the inevitable inconveniences and impositions of work without complaining'' (Organ, 1990, p. 96).…”
mentioning
confidence: 99%
“…Graham and Van Dyne (2006), for example, discuss responsible political participation in organizations in terms of civic virtue, a form of organizational citizenship behavior. In turn, they consider two important prosocial and proactive forms of civic virtue, gathering information and exercising influence, which are supposed to exert beneficial results on both individuals and organizations.…”
Section: Reframing Politics In Organizational Lifementioning
confidence: 99%